IDENTIFICATION OF NURSE KNOWLEDGE AND ATTITUDE TOWARDS PALLIATIVE CARE IN RSUD Dr. M. YUNUS BENGKULU - Qurratul A'yuni; Tuti Anggriani Utama; Maiyulis Maiyulis (Universitas Bengkulu, 2021)
This study aims to identify the knowledge and attitudes of nurses towards palliative care in Dr. M. Yunus Bengkulu. The type and research method used is descriptive quantitative with a cross sectional study. The research subjects were 63 nurses in the Intensive Care Unit (ICU), the Intensive Coronary Care Unit (ICCU), the Seruni Room and the Hemodialysis Room (HD) at Dr. M. Yunus Bengkulu. Data collection techniques using a questionnaire (Questionnaire). The data analysis technique used the Univariate technique. There are 3 types of data processing techniques, namely; Editing, Coding, and Scoring. The validity test for the Knowledge level questionnaire used the The Palliative Care Quiz for Nurses- Indonesian (PCQN-I) questionnaire while for attitudes the Frommelt's Attitude Toward Care of The Dying Care Form B (FATCOD-B) questionnaire was used to measure knowledge. with a result of 0.71 (Kuder-Richardson Formula Score) while to measure attitudes the result is 0.68 (Alpha Cronbach). The results showed that the nurses studied in 4 rooms in RSUD M. Yunus Bengkulu were mostly female, namely 65%, then the latest education of nurses was 48%, the majority were Ners and 60,3%, the nurses studied were average -the average age ? 35 - 50. The results obtained the knowledge and attitude value of 63 nurses in 4 rooms of RSUD Dr. M. Yunus Bengkulu as many as 52% of respondents have less knowledge and most of the respondents have a negative attitude towards palliative care.. It can be concluded that the nurses studied have less knowledge and attitudes towards palliative care.